A Multidisciplinary Approach to Motor Learning and Sensorimotor Adaptation - Sean Kevin Meehan (Frontiers Research Topics, 2015)
The plasticity of the living matter of our nervous system, in short, is the reason why we do a thing with difficulty the first time, but soon do it more and more easily, and finally, with sufficient practice, do it semi-mechanically, or with hardly any consciousness at all. William James, 1899. It is over 100 years since James described the acquisition of skill. How much, or how little, have recent advances in science changed the way we think about skill learning? What theories and ideas do we still hold dear and which have we discarded? Advances in neuroimaging over the past 20 years have provided insight into the dynamic neural processes underlying human motor skill acquisition, focusing primarily on brain networks that are engaged during early versus late stages of learning. What has been challenging for the field is to tightly link these shifting neural processes with what is known about measureable behavioral changes and strategic processes that occur during learning. The complex nature of behavior and strategy in motor learning often result in a trade-off between experimental control and external validity. The articles assembled for this special issue cut across a number of related disciplines and investigate skill learning across multiple domains. The broad range of theoretical, analytical and methodological approaches offer complementary approaches that can be exploited to develop integrated models of skilled learning. It is our hope that this collection inspires innovation and collaboration amongst researchers, and thereby, accelerates development of societally relevant translational paradigms.